PENGARUH KINERJA, KEBIJAKAN, UKURAN, KEPEMILIKAN MANAJERIAL DAN PERTUMBUHAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN - Suryanto; Dewi Hartati (E-Jurnal Akuntansi TSM, 2022)
This research was conducted to examine the effect of company’s performance that consists of liquidity, profitability and activity, company’s policy that consists of investment policy, financing policy and dividend policy, and other variables like company size, managerial ownership, and company growth on firm value. Population of this research are non-financial companies listed on the Indonesia Stock Exchange for the period 2015-2017. This study used samples of 66 companies selected using purposive sampling method. The data used in this study are secondary data of the company financial statements and other reports obtained from the IDX website. Multiple linear regression is used to analyze data in this study. The results of this study was revealed that profitability, investment policy, financing policy, and company growth have influence on firm value. Whereas liquidity, activity, dividend policy, firm size and managerial ownership have no influence on company value